Corporate governance ratings and financial performance: evidence from Australia. (2014) - Baxter, Peter
This study investigates the relationship between the corporate governance ratings of Australian publicly listed companies and their financial performance. The data used in the study includes all companies listed in the Horwath Corporate Governance Report across the years 2006 to 2008. Company financial performance was measured by three alternative variables, while the main independent variables of interest were the company rankings and star ratings from the Horwath Report. The results of the study provide consistent evidence over the three years that companies with higher quality corporate governance have higher levels of financial performance. The study therefore makes important contributions to the existing literature and will be of value to investors, companies and regulators in assessing the extent to which a corporate governance ratings system explains variations in company financial performance.